Longitudinal characterization of HIV-1 pol-gene in treatment-naïve men-who-have-sex-with-men from acute to chronic infection stages - Cevallos, Cintia Gisela (2020)
HIV-1 is characterized by its ability to mutate and recombine even at polymerase (pol) gene. However, pol-gene diversity is limited due to functional constraints. The aim of this study was to characterize longitudinally, by next-generation sequencing (NGS), HIV-1 variants based on pol-gene sequences, at intra- and inter-host level, from acute/early to chronic stages of infection, in the absence of antiretroviral therapy. Ten men who have sex with men (MSM) were recruited during primary infection and yearly followed for five years. Even after a maximum of a five-year follow-up period, the phylogenetic analysis of HIV-1 pol-gene sequences showed a host-defined structured pattern, with a predominance of purifying selection forces during the follow-up. MSM had been acutely infected by different HIV-1 variants mainly ascribed to pure subtype B, or BF recombinant variants and showed different genetic mosaicism patterns that last until the chronic stage, representing a major challenge for prevention strategies.